Human Capital Transformation In Global Migration: Insight From The Lived Experience Of Indonesian Workers In Taiwan - Sri Astuti Nasir (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
Labor migration has become an essential part of Indonesian society and plays a significant role in supporting the national economy. Beyond economic motives, migration also represents a profound process of learning and personal transformation. This study aims to explore how overseas work experiences contribute to human capital transformation among Indonesian migrant workers in Taiwan. Using a qualitative approach with a single case study design, this research examines the lived experience of an Indonesian migrant worker through online interviews and thematic analysis. The findings reveal that the motivation to migrate is initially driven by economic needs and family aspirations but gradually evolves into a process of self-discovery and personal growth. Cultural adaptation fosters the ability to interact within different environments, internalize new values, and build emotional resilience. Workplace learning helps workers strengthen their technical skills, communication abilities, and professionalism, enriching their overall human capacity. These interconnected processes show that migration is not merely an economic movement but a human journey toward growth and empowerment. The study concludes that migration has strong potential to enhance human capital and should be supported through sustainable policies and training programs that emphasize capacity development and migrant workers’ well-being.